Subjective video quality evaluation for user generated contents via textual prompts - Ang, Dario (Nanyang Technological University, 2024)
The explosion of user-generated content (UGC) videos has transformed the online landscape. Platforms like TikTok and YouTube overflow with UGC, offering a diverse range of content consumed by billions of viewers. While this presents exciting avenues for creative expression and content consumption, it also introduces significant challenges in assessing video quality.